Fashion designs inspired by ecological influences - Roaya Hameed Yaseen (الاكاديمي)
Ecology is the science that summarizes the fundamental relationship between man and nature to know the sensory repercussions that occur to man and are reflected in his daily behavior and his production, which varies in its evidence according to what researchers reach in this way. We wanted to address in this research the most important ecological influences in the design of fabrics and fashions, and we found The environment is the most comprehensive container for the aesthetic concept that we seek , In all cases, we return to the environment as the pulsating nerve of everything that a person sees, and at the forefront of the things that are affected by the environment are the arts and fashion design in light of the sensory response between the person and the components of the environment, and natures, colors, compositions, and materials emerge from that, as we see the environmental influences on creative production in general and Fashion in particular because it relates to our daily lives , The theoretical framework included two sections, the first of which was concerned with the concept of ecology, while the second section was concerned with the ecological influences on the design of fabrics and fashions by getting to know the most important fashion designers in the world who were influenced by the concept of ecology in light of the sensory response between humans and the components of the environment, and the natures, colors, compositions and materials that emerge from that, from here. The researcher reached the most important results, including that the design results achieved by fashion designers, which are consistent with the latest findings in ecology, express extremely creative future prospects..